(untitled) (Revista de História Regional, 2025)
Since it was a political-administrative and territorial rearrangement with national repercussions, the creation of a new province required complex political negotiations in the Brazilian parliament. During the 19th century, only two experiences were successful in this regard: Paraná and Amazonas. On that same occasion, the “good men” of the Municipal Council of Campos dos Goytacazes, in the province of Rio de Janeiro, maintained the desire that their city could become the capital of a new province. This article analyzes the political trajectory of this proposal to create the province of Goytacazes, which did not achieve the expected success. Finally, it considers how this ambition, which was the result of the local elite’s perception of the discrepancy between the importance of their municipality and the treatment received by the provincial authorities (Assembly and Government), came up against a context in which the liberal constitutional political culture required new support networks and new interpretations of political action.